2016
DOI: 10.1093/ehjci/jew284
|View full text |Cite
|
Sign up to set email alerts
|

3D echocardiographic reference ranges for normal left ventricular volumes and strain: results from the EACVI NORRE study

Abstract: The NORRE study provides applicable 3D echocardiographic reference ranges for LV function assessment. Our data highlight the importance of age- and gender-specific reference values for both LV volumes and strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 22 publications
5
53
0
Order By: Relevance
“…The decrease in LV 3D volumes with age was counterbalanced by an augment in LVEF with advancing age (50,59,95) as occurred also for RV (82). Relationships of left atrial 3D volumes were opposite to the ones observed for the ventricles.…”
Section: D Echocardiographic Parametersmentioning
confidence: 81%
See 4 more Smart Citations
“…The decrease in LV 3D volumes with age was counterbalanced by an augment in LVEF with advancing age (50,59,95) as occurred also for RV (82). Relationships of left atrial 3D volumes were opposite to the ones observed for the ventricles.…”
Section: D Echocardiographic Parametersmentioning
confidence: 81%
“…In fact, LA 3D volumes increased with age (52,58,81) accompanied by a reduction of LAEF with age (58). LV volumes and mass were higher in men even after normalisation for BSA (51,52,95). The lower volumes in women were counterbalanced by the higher LVEF, however, the stroke volume remained higher in men (51,95).…”
Section: D Echocardiographic Parametersmentioning
confidence: 97%
See 3 more Smart Citations